2013
DOI: 10.1142/s0219498812502192
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Ideal Generated by a Quadratic Multivariate Function Over Gf(3)

Abstract: Let K be the field GF(3). We calculate the growth of the ideal Aλ where A is the algebra of functions from Kn → Kn and λ is a quadratic function. Specifically we calculate dim Akλ where Ak is the space of polynomials of degree less than or equal to k. This question arises in the analysis of the complexity of Gröbner basis attacks on multivariate quadratic cryptosystems such as the Hidden Field Equation systems. We also prove analogous results over the associated graded ring [Formula: see text] and state conjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The result is proved here for q an odd prime. When q = 2 the same result is proved implicitly in [4]. There are a number of directions in which one might want to extend this result and we comment briefly now on each of these.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…The result is proved here for q an odd prime. When q = 2 the same result is proved implicitly in [4]. There are a number of directions in which one might want to extend this result and we comment briefly now on each of these.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, it was shown that non-trivial annihilators of λ occur only in degrees n/2 and n/2 + 1 and have dimension n/2 in both cases. Analogous results were proved for the case q = 3 in [4] and conjectures were made concerning the general case. We prove these conjectures in the case where q is an arbitrary odd prime.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations